Engaging post-compulsory education students in online language courses: a systematic review - Peltola, Katja; Veermans, Marjaana; Routarinne, Sara; Jaaksola, Sara (SPRINGER HEIDELBERG, 2026)
The popularity of online language courses in post-compulsory education, especially in higher education, has increased due to more advanced technological solutions, cost effectiveness and digitalisation. Especially in online learning, student engagement is a key factor for successful learning. This article presents a systematic review of student engagement in online language learning over the last decade. Searches were conducted in 14 central databases. A total of 943 studies were identified, of which 21 met the inclusion criteria. These studies were analysed using content analysis, focusing on the conceptualisation of student engagement, factors related to student engagement, and implications of the findings presented in the reviewed studies. The results of the analysis showed that student engagement in online learning environment is in many cases studied using frameworks and conceptualisations created for face-to-face environment. The results implied that student engagement in online learning environment is influenced by various psychological (e.g. self-efficacy) and pedagogical (e.g. course design) factors. The online learning environment was found to be more student-centred than the face-to-face environment and the three most central factors influencing student engagement seem to be self-directed learning, collaboration, and the role of the teacher. The findings indicate that future research should concentrate on the further development of existing frameworks that have been specifically designed for studying student engagement in the online learning environment. Further research is also needed on the positioning of student engagement and its closely related psychological constructs.